Tough double-network hydrogel as well as preparation method and application thereof

Through the synergistic effect of frozen casting and salting out effects, a strong dual network hydrogel was prepared, solving the problems of low mechanical properties and complex preparation process of hydrogel meniscus alternatives in the prior art, and achieving high strength, biocompatibility and antibacterial and antioxidant functions.

CN119798709APending Publication Date: 2025-04-11王梦冉
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411783263.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to prepare hydrogel meniscus alternatives with high strength, high stiffness, excellent biocompatibility, low wear and inherent antibacterial and antioxidant functions, and the preparation process is complicated and toxic chemical crosslinking agents are used.

Method used

Through the synergistic effect of frozen casting and salting out effects, a strong dual network hydrogel is designed and manufactured. A mixed aqueous solution of polymers, polysaccharides and polyphenols is frozen-thawed and immersed in the salt solution to form a dual network structure with high mechanical properties and biological activity.

Benefits of technology

The preparation of strong dual network hydrogels is realized, with excellent mechanical properties, biocompatibility, low wear characteristics and inherent antibacterial and antioxidant functions, and is suitable for meniscus alternatives and other soft-supporting tissue scaffolds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798709A_ABST
    Figure CN119798709A_ABST
Patent Text Reader

Abstract

The invention discloses tough double-network hydrogel as well as a preparation method and application thereof, and belongs to the technical field of polymer hydrogel. A mixed aqueous solution in which a high-molecular polymer, polysaccharide and polyphenol are dissolved is subjected to freezing-unfreezing and soaking in a salt solution to obtain the high-molecular-weight polysaccharide-polyphenol salt solution. Through detection, the material has excellent mechanical properties: the tensile strength reaches 28.9 MPa, the fracture toughness reaches 271.2 MJ / m <-3 >, the compressive strength reaches 152.8 MPa, and the toughness reaches 25.4 MJ / m <-3 >; excellent biocompatibility, low wear characteristic, inherent antibacterial and antioxidant biological activities and the like are realized. In-vivo experiments show that as a meniscus substitute, the material can effectively relieve cartilage surface abrasion and slow down the development of osteoarthritis, which indicates that the material has huge application potential in the fields of meniscus substitutes, other soft support tissue scaffolds and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer hydrogels, and in particular relates to a strong double network hydrogel and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] The meniscus is a wedge-shaped articular cartilage between the femoral condyle and the tibial plateau, which is subjected to a variety of forces from all directions, such as compression, tension, tearing, etc. At present, due to the arrival of an aging society and the increase in sports injuries, meniscus injury and degeneration are considered to be one of the serious musculoskeletal diseases, which may lead to knee dysfunction, significant pain and even disability. The most commonly used method for treating meniscus injury is meniscectomy. Although meniscectomy can partially relieve pain, there is still a risk of articular cartilage degeneration and even osteoarthritis. Therefore, it is very necessary to design and construct a meniscus substitute with a similar geometry to the natural meniscus, high mechanical properties and swelling stability under physiological conditions to partially or completely restore its function after meniscectomy, thereby maintaining the health of the knee joint.

[0004] Polycaprolactone is a thermoplastic polymer approved by the U.S. Food and Drug Administration with excellent mechanical properties, low melting point, slow degradation rate and non-toxic degradation products. At present, the preparation of polycaprolactone scaffolds based on 3D printing technology for meniscus injury repair has been reported. However, polycaprolactone meniscus scaffolds can cause severe wear on the femoral and tibial cartilage surfaces due to their high compressive stiffness, which may further aggravate the progression of osteoarthritis. 3D printed hydrogels have been developed as meniscus substitutes because hydrogels have similar physicochemical properties to natural soft tissues. It is well known that hydrogels printed by extrusion usually suffer from severe mechanical weakening compared with their cast counterparts due to defects formed during the printing process or weak adhesion between sequentially deposited layers. For example, in “3D Printing of Structured Functional Hydrogels and Their Properties” (Jiang Pan. 3D Printing of Structured Functional Hydrogels and Their Properties [D]. University of Chinese Academy of Sciences, 2021.), polyvinyl alcohol (PVA) and soluble short-chain chitosan (CS) were used to prepare 3D printing hydrogel inks, and complex three-dimensional hydrogel structures were printed using ink direct writing technology. Finally, PVA physical crystal networks and chitosan ion cross-linked networks were constructed by freeze-thaw cycles and sodium citrate solution coordination cross-linking, respectively. Its mechanical properties are low and still need to be improved. Toxic chemical cross-linkers and additives are used in the preparation process, the preparation steps are complicated, and the material itself has no antibacterial and anti-inflammatory functions. Therefore, it remains a challenge to develop a simple strategy to prepare high-strength multifunctional hydrogel meniscus substitutes. Summary of the invention

[0005] In order to address the deficiencies of the prior art, the purpose of the present invention is to provide a strong double-network hydrogel and a preparation method and application thereof. The present invention designs and manufactures a double-network hydrogel with high strength, high stiffness, excellent biocompatibility, low wear and inherent antibacterial and antioxidant biological activities based on the synergistic effect of freeze-casting and salting-out effect. The double-network hydrogel has great application potential in the fields of meniscus substitutes and other soft support tissue scaffolds.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] The first aspect of the present invention provides a strong double network hydrogel, which is obtained by freezing and thawing a mixed aqueous solution containing a high molecular weight polymer, a polysaccharide and a polyphenol, and immersing it in a salt solution;

[0008] In the mixed aqueous solution, the concentration of the high molecular polymer is 1-40wt%, the concentration of the polysaccharide is 0.1-10wt%, and the concentration of the polyphenol is 0.1-10wt%.

[0009] In some embodiments of the present invention, the high molecular weight polymer is selected from one or more of polyvinyl alcohol, gelatin, polyvinyl pyrrolidone, polyglutamic acid and / or hydroxypropyl methylcellulose, preferably polyvinyl alcohol.

[0010] In some embodiments of the present invention, the polysaccharide is selected from one or more of carboxymethyl chitosan, sodium alginate, chitosan, pectin and / or carboxymethyl cellulose, preferably carboxymethyl chitosan.

[0011] In some embodiments of the present invention, the polyphenol is selected from one or more of tannic acid, gallic acid, epigallocatechin gallate, catechin and / or anthocyanin, preferably tannic acid.

[0012] In some embodiments of the present invention, the salt is selected from one or more of sodium chloride, sodium citrate, sodium sulfate, sodium iodide, sodium carbonate, sodium nitrate, potassium chloride, lithium chloride, calcium chloride and / or magnesium chloride, preferably sodium chloride.

[0013] In some embodiments of the present invention, in the mixed aqueous solution, the concentration of the high molecular polymer is 10-20wt%, the concentration of the polysaccharide is 0.5-4wt%, and the concentration of the polyphenol is 0.5-4wt%.

[0014] In some embodiments of the present invention, the high molecular polymer is polyvinyl alcohol, the polysaccharide is carboxymethyl chitosan, and the polyphenol is tannic acid.

[0015] In some embodiments of the present invention, the high molecular weight polymer is polyvinyl alcohol, the polysaccharide is carboxymethyl chitosan, and the polyphenol is tannic acid;

[0016] In the mixed aqueous solution, the concentration of polyvinyl alcohol is 20 wt %, the concentration of carboxymethyl chitosan is 3 wt %, and the concentration of tannic acid is 2 wt %.

[0017] The second aspect of the present invention provides a method for preparing the above-mentioned strong double network hydrogel, comprising:

[0018] dissolving high molecular polymer, polysaccharide and polyphenol in water to obtain a mixed solution;

[0019] The mixed solution is subjected to a freeze-thaw method to form a double network hydrogel;

[0020] The double network hydrogel is immersed in a salt solution to obtain a strong double network hydrogel.

[0021] In some embodiments of the present invention, the stirring is stirring at 85-95° C. for 1-6 h, preferably 4 h.

[0022] In some embodiments of the present invention, the freezing is freezing at -20°C for 6-24 hours, preferably freezing at -20°C for 12 hours.

[0023] In some embodiments of the present invention, the thawing is thawing at 25°C for 2-12 hours, preferably thawing at 25°C for 6 hours.

[0024] In some embodiments of the present invention, the salt is selected from one or more of sodium chloride, sodium citrate, sodium sulfate, sodium iodide, sodium carbonate, sodium nitrate, potassium chloride, lithium chloride, calcium chloride and / or magnesium chloride, preferably sodium chloride.

[0025] In some embodiments of the present invention, the concentration of the sodium chloride solution is: 1-5.43 mol / L, and more preferably 5.43 mol / L.

[0026] In some embodiments of the present invention, the double network hydrogel is immersed in the saline solution for 1-24 hours, more preferably for 12 hours.

[0027] The third aspect of the present invention provides a use of the above-mentioned strong and tough double network hydrogel or the strong and tough double network hydrogel prepared by the above-mentioned preparation method in preparing a soft supporting tissue scaffold.

[0028] In some embodiments of the invention, the soft supporting tissue scaffold comprises a meniscus substitute.

[0029] The beneficial effects of the present invention are:

[0030] The present invention provides a strong and tough double network hydrogel. The double network hydrogel with a crystalline domain is prepared by a freeze-thaw method. When it is immersed in a salt solution, the salting-out effect will further entangle the molecular chains, thereby obtaining a strong and tough double network hydrogel, thus realizing the transformation from a weak and brittle hydrogel to a strong and tough hydrogel. After testing, the strong and tough double network hydrogel provided by the present invention has excellent mechanical properties: the tensile strength can reach 28.9MPa, and the fracture toughness can reach 271.2MJ / m -3 , compressive strength can reach 152.8MPa, toughness can reach 25.4MJ / m -3 . The strong double network hydrogel has excellent biocompatibility, low wear characteristics and inherent antibacterial and antioxidant biological activities. In vivo experiments have shown that the strong double network hydrogel meniscus substitute can effectively alleviate the wear of the cartilage surface and slow down the development of osteoarthritis, indicating that it has great application potential in the fields of meniscus substitutes and other soft support tissue scaffolds.

[0031] The method for preparing the strong and tough double network hydrogel provided by the present invention is simple and easy to implement. The present invention provides a simple, controllable and universal method for preparing a fully physically cross-linked double network hydrogel with high mechanical properties.

[0032] Advantages of additional aspects of the present invention will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0034] Figure 1 Schematic diagram of the preparation of high-strength PCTN double network hydrogel in Example 1 of the present invention and its biomedical application as a meniscus substitute;

[0035] Figure 2 SEM images of the PCTN double network hydrogel prepared in Example 1 of the present invention and the P hydrogel, PC hydrogel, and PCT hydrogel (Comparative Example 1);

[0036] Figure 3 The visual appearance of the P hydrogel, PC hydrogel and PCT hydrogel in the examples of the present invention and the comparative examples before and after immersion in a saturated NaCl solution, the photos of the PCTN double network hydrogel in the shape of different marine animals and the macroscopic photos of the mechanical properties;

[0037] Figure 4 : The tensile stress-strain curves of the P hydrogel, PC hydrogel and PCT hydrogel in the examples of the present invention and the comparative examples before and after immersion in a saturated NaCl solution;

[0038] Figure 5 The tensile mechanical property curves of the PCTN double network hydrogels with different PVA (A), CMCS (B) and TA (C) concentrations in Examples 2, 3 and 4 of the present invention;

[0039] Figure 6 The lubrication properties of the PCTN double network hydrogel obtained in Example 1 of the present invention, the PN hydrogel obtained in Comparative Example 2, and the PCN hydrogel obtained in Comparative Example 3;

[0040] Figure 7 The water contact angle photographs of the PCTN double network hydrogel obtained in Example 1 of the present invention, the PN hydrogel obtained in Comparative Example 2, and the PCN hydrogel obtained in Comparative Example 3;

[0041] Figure 8 The antioxidant properties of the PCTN double network hydrogel obtained in Example 1 of the present invention, the PN hydrogel obtained in Comparative Example 2, and the PCN hydrogel obtained in Comparative Example 3; wherein A is the absorption spectrum of the DPPH solution and its color change diagram, and B is the DPPH free radical scavenging ability;

[0042] Fig. 9 The in vitro cytotoxicity of the PCTN double network hydrogel obtained in Example 1 of the present invention, the PN hydrogel obtained in Comparative Example 2, and the PCN hydrogel obtained in Comparative Example 3; wherein A is a cell viability graph after cells are incubated with the three hydrogels, and B is a cell live / dead staining analysis after cells are incubated with the three hydrogels;

[0043] Fig.10 Schematic diagram of the PCTN double network hydrogel obtained in Example 1 of the present invention as a meniscus substitute in vivo and the operating steps of implanting the PCTN double network hydrogel meniscus substitute in a rat model;

[0044] Fig.11 The PCTN double network hydrogel obtained in Example 1 of the present invention, the PN hydrogel obtained in Comparative Example 2, and the PCN hydrogel obtained in Comparative Example 3 are macroscopic observation photos of the PCTN double network hydrogel obtained in Example 1 of the present invention, implanted in the femoral condyle and tibial plateau joints 8 weeks after surgery as meniscus substitutes in vivo;

[0045] Fig.12 H&E staining, Masson staining and SOFG staining images of the knee joints of the PCTN double network hydrogel in Example 1 of the present invention, the PN hydrogel obtained in Comparative Example 2, and the PCN hydrogel obtained in Comparative Example 3 as meniscus substitutes 8 weeks after surgery;

[0046] Fig.13 The immunohistochemical staining images of COL-II and MMP-13 in vivo treatment of the PCTN double network hydrogel in Example 1 of the present invention, the PN hydrogel obtained in Comparative Example 2, and the PCN hydrogel obtained in Comparative Example 3 as meniscus substitutes are shown. DETAILED DESCRIPTION

[0047] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0048] Example 1

[0049] A method for preparing a strong double network hydrogel based on the synergistic effect of freeze casting and salting-out effect comprises the following steps:

[0050] (1) Accurately weigh 10.0 g PVA, 1.5 g CMCS and 1.0 g TA, add them into 37.5 g water, and stir them in a 90 °C water bath for 4 h to obtain a PVA / CMCS / TA mixed solution.

[0051] (2) Cast the above dissolved mixture into the desired mold. The PCT double network hydrogel is formed by the classic freeze-thaw method (i.e., placed at -20°C for 12 hours and then thawed at room temperature). Finally, the prepared PCT double network hydrogel is immersed in a saturated NaCl solution for 12 hours. The salting-out effect will further entangle the molecular chains to obtain the PCTN double network hydrogel. Figure 1 The obtained strong double network hydrogel is abbreviated as PCTN.

[0052] Example 2

[0053] A method for preparing a strong double-network hydrogel based on the synergistic effect of freeze casting and salting-out effect, which is different from Example 1 in that the mass of added CMCS is changed from 1.5g to 2.0g, 1.0g, 0.5g or 0.25g, the total mass of the mixed solution is 50g, and the remaining steps are consistent with Example 1.

[0054] Example 3

[0055] A method for preparing a strong double-network hydrogel based on the synergistic effect of freeze casting and salting-out effect, which is different from Example 1 in that the mass of PVA is changed from 10.0g to 7.5g or 5g, the total mass of the mixed solution is 50g, and the remaining steps are consistent with Example 1.

[0056] Example 4

[0057] A method for preparing a strong double-network hydrogel based on the synergistic effect of freeze casting and salting-out effect, which is different from Example 1 in that the mass of added TA is changed from 1.0g to 0.5g, 0.25g, 1.5g or 2g, the total mass of the mixed solution is 50g, and the remaining steps are consistent with Example 1.

[0058] Example 5

[0059] A method for preparing a strong double-network hydrogel based on the synergistic effect of freeze casting and salting-out effect, which differs from Example 1 in that the number of freeze-thaw cycles is changed from 1 to 3.

[0060] Example 6

[0061] A method for preparing a strong double network hydrogel based on the synergistic effect of freeze casting and salting-out effect, which differs from Example 1 in that the time for immersing the PCT double network hydrogel in a saturated NaCl solution is changed from 12 h to 24 h.

[0062] Example 7

[0063] A method for preparing a strong double-network hydrogel based on the synergistic effect of freeze casting and salting-out effect, which differs from Example 1 in that the saturated NaCl solution is replaced by a saturated sodium citrate solution.

[0064] Comparative Example 1

[0065] In order to compare the effects of immersion and non-immersion in saturated NaCl solution on the mechanical properties of hydrogels, comparative example 1 was set. The difference between comparative example 1 and example 1 is that immersion in saturated NaCl solution is not performed, and the remaining steps are consistent with example 1. The obtained hydrogel is abbreviated as PCT.

[0066] Comparative Example 2

[0067] A method for preparing a strong double network hydrogel based on the synergistic effect of freeze casting and salting-out effect, which is different from Example 1 in that: 12.5 g of PVA is accurately weighed and added to 37.5 g of water, and stirred for 4 hours in a 90° C. water bath, and the remaining steps are consistent with Example 1. The obtained hydrogel is abbreviated as PN.

[0068] Comparative Example 3

[0069] A method for preparing a strong double network hydrogel based on the synergistic effect of freeze casting and salting-out effect, which is different from Example 1 in that: 11.0 g PVA and 1.5 g CMCS are accurately weighed and added to 37.5 g water, and stirred for 4 h in a 90° C. water bath, and the remaining steps are consistent with Example 1. The obtained hydrogel is abbreviated as PCN.

[0070] Experimental Example 1: Hydrogel Performance Testing

[0071] The PCTN double network hydrogels used in the following experimental examples are all the PCTN double network hydrogels prepared in Example 1.

[0072] The meanings of the hydrogels in the following experimental examples are:

[0073] P represents PVA hydrogel; PN represents the hydrogel after the PVA hydrogel is soaked in NaCl, that is, the hydrogel obtained in Example 2 is compared.

[0074] PC represents the hydrogel composed of PVA and CMCS; PCN represents the hydrogel composed of PVA and CMCS after being soaked in NaCl, that is, the hydrogel obtained in Comparative Example 3.

[0075] PCT represents the hydrogel composed of PVA, CMCS and TA, that is, the hydrogel obtained in Comparative Example 1, and PCTN represents the hydrogel composed of PVA, CMCS and TA after being soaked in NaCl, that is, the hydrogel obtained in Example 1.

[0076] (1) SEM test

[0077] The PCTN double network hydrogel obtained in Example 1 was characterized in terms of morphology. Figure 2It can be seen that the newly formed physical network helps to make the structure of the hydrogel more compact. For the P hydrogel, the pore size is large and uneven. After adding CMCS, the pore size is slightly reduced. After adding TA, the pore size is further reduced due to the formation of a double network. Compared with other hydrogels, the PCTN double network hydrogel has the smallest pore size, indicating that a denser network structure is formed due to further chain entanglement.

[0078] (2) Mechanical properties test

[0079] First, the appearance and mechanical properties of the PCTN double network hydrogel obtained in Example 1 were macroscopically characterized. Figure 3 As shown, the hydrogels became opaque and shrank in volume after immersion compared to the hydrogels before immersion in saturated NaCl solution. The reduction in transparency is attributed to the chain entanglement of the molecular chains. The volume shrinkage is attributed to the osmotic pressure difference between the hydrogel and the surrounding solution. Interestingly, these hydrogels have attractive free-formability properties and can adapt to any customized shapes, such as starfish, shells, and conchs. It is worth noting that the PCTN double network hydrogels have excellent mechanical properties, can withstand the stretching and compression of heavy objects and have high elasticity.

[0080] Secondly, quantitative tensile properties and fracture toughness tests were performed on P hydrogel, PC hydrogel and PCT hydrogel before and after immersion in saturated NaCl solution ( Figure 4 After being immersed in saturated NaCl solution, the mechanical properties of the hydrogels were significantly improved, indicating that immersion in saturated NaCl solution and non-immersion in saturated NaCl solution had a significant effect on the mechanical properties of the hydrogels. After the PCT hydrogels were immersed in saturated NaCl solution, the tensile fracture stress and strain increased from 0.21MPa and 203% ( Figure 4 A) increased to 3.95MPa and 420% ( Figure 4 B), which further proves that the salting-out effect plays an important role in enhancing the mechanical properties of hydrogels.

[0081] Then, the PCTN double network hydrogels with different PVA, CMCC and TA concentrations were quantitatively tested for tensile properties and fracture toughness ( Figure 5 ).Depend on Figure 5 As shown in Figure A, when the PVA concentration is 20%, the tensile strength and tensile strain of the PCTN double network hydrogel reach the maximum, which are 28.9MPa and 1602%, respectively. Figure 5 As shown in Figure B, when the CMCC concentration is 3%, the tensile strength and tensile strain of the PCTN double network hydrogel reach the maximum, which are 28.9MPa and 1602%, respectively. Figure 5As shown in Figure C, when the concentration of TA is 2.0wt%, the tensile strength and tensile strain of PVA / CMCS / TA-NaCl double network hydrogel reach the maximum, which are 28.9MPa and 1602%, respectively. At this time, the fracture toughness of PCTN double network hydrogel can reach 271.2MJ / m 3 .

[0082] (3) Lubricating properties of hydrogels

[0083] In engineering meniscus substitutes, in addition to strength and stiffness, lubricity to reduce joint wear cannot be ignored. This experiment characterizes the lubricity of PCTN double network hydrogels through friction tests and water contact angle tests. Figure 6 As shown in the figure, the friction coefficient (COF) of PCTN double network hydrogel is lower than that of PN and PCN hydrogels. The low COF is attributed to the hydrophilicity of CMCS molecules and TA. The charged surface of PCTN double network hydrogel network can also increase the thickness of the water lubrication layer between the gel and the opposite surface, thereby reducing the COF value. Water contact angle measurement experiments further show that ( Figure 7 ), the PCTN double network hydrogel showed a lower water contact angle compared with the PN and PCN hydrogels, indicating that it has a more hydrophilic surface, which facilitates the formation of a hydration layer and thus leads to a lower COF value.

[0084] (4) Antioxidant test of hydrogel

[0085] It is reported that after meniscus injury, a significant inflammatory reaction will occur in the joint cavity. Inflammation can cause oxidative stress and increase the level of reactive oxygen in the knee joint. This oxidative stress may hinder the differentiation of mesenchymal stem cells and the proliferation of chondrocytes, causing knee joint dysfunction. TA has excellent antioxidant properties, which can scavenge free radicals and reduce the damage caused by oxidative stress. Therefore, the antioxidant capacity of PCTN double network hydrogel was evaluated by DPPH scavenging experiment ( Figure 8 After the PCTN double network hydrogel was incubated in the DPPH solution for 30 min, the color of the DPPH solution changed from purple to yellow, and the characteristic absorption peak of DPPH at a wavelength of 517 nm also dropped sharply ( Figure 8 Compared with PN (1.86%) and PCN (6.12%) hydrogels, PCTN double network hydrogel has the strongest DPPH free radical scavenging ability (85.46%) ( Figure 8 (middle B).

[0086] (5) Biocompatibility of hydrogels

[0087] Good biocompatibility is the premise for exploring hydrogels as meniscus substitutes. In order to prove the applicability of PCTN double network hydrogel in biomedicine, this experiment tested the cell compatibility of PCTN double network hydrogel with NIH-3T3 cells by MTT test and cell live / dead staining method ( Fig. 9 After 24 h of incubation, PN, PCN, and PCTN double network hydrogels all showed that the cell viability of NIH-3T3 exceeded 95% ( Fig. 9 A), indicating that all hydrogels have good cell compatibility. Cell live / dead staining analysis showed that there were almost no dead cells in all groups during the culture process, and the cells were spindle-shaped after 24 hours of culture ( Fig. 9 In summary, the above results indicate that all hydrogels have good cell compatibility, which is crucial for their further application in vivo.

[0088] (6) The therapeutic effect of hydrogel as a meniscus substitute in vivo

[0089] In order to verify the therapeutic effect of PCTN double network hydrogel as a meniscus substitute in vivo. Rats were randomly divided into 5 groups, namely sham group (sham), control group (control), PN group, PCN group and PCTN double network group. After 8 weeks of treatment, imaging and histological evaluation were performed to reflect the therapeutic effect of PCTN double network hydrogel as a meniscus substitute in vivo. The implantation process of meniscus substitute in rat model is as follows Fig.10 As shown. 8 weeks after surgery, the femoral condyle and tibial plateau were harvested and macroscopic observation and photography were performed to evaluate the protective effect of the PCTN double network hydrogel scaffold on cartilage. Fig.11 As shown, the articular surface of the sham group was smooth and intact, and there was no sign of inflammatory hyperplasia of the synovium. However, in the control group, the cartilage of the tibial plateau articular surface and the femoral condyle articular surface showed severe exfoliation and defects, accompanied by a large amount of synovial fibrous tissue hyperplasia. Compared with the control group, the cartilage exfoliation and defects in the PN hydrogel group were alleviated, but there was still a large amount of synovial fibrous tissue hyperplasia. In the PCN hydrogel group, the synovial fibrous tissue hyperplasia was significantly reduced. The PCTN double-network hydrogel group further improved the condition of synovial fibrous tissue hyperplasia, and the exfoliation and defects of articular cartilage were also significantly improved, indicating that the implantation of PCTN double-network hydrogel scaffolds can well protect cartilage lesions.

[0090] In order to more clearly observe the protective effect of PCTN double network hydrogel scaffold on tibial and femoral cartilage, H&E staining, Masson staining and SOFG staining were performed in this experimental case ( Fig.12). From the staining results, the articular cartilage section of the sham group was smooth and intact, and there was no inflammatory hyperplasia of the synovial tissue. The control group that did not undergo artificial meniscus replacement showed severe cartilage wear, sparse subchondral bone trabeculae, and inflammatory hyperplasia of the synovial tissue. Compared with the control group, the destruction of the articular cartilage in the PN hydrogel group was significantly reduced, and the subchondral bone trabeculae were thicker and denser, but there was still obvious inflammatory hyperplastic tissue. Compared with the PN hydrogel group, the inflammatory hyperplasia of the synovial fibrous tissue in the PCN hydrogel group was significantly reduced. Compared with the PCN hydrogel group, the PCTN double network hydrogel group had further improved the integrity of the articular cartilage and reduced inflammatory hyperplasia, indicating that the PCTN double network hydrogel significantly reduced cartilage surface wear and degradation within 8 weeks and has the potential to prevent the progression of osteoarthritis.

[0091] Finally, this experiment detected the protein expression levels of articular cartilage biomarkers COL-II and MMP-13 by immunohistochemical staining ( Fig.13 ). The results showed that in the sham group, COL-II was highly expressed at the base of the articular cartilage, while MMP-13 was at a low expression level; in comparison, the expression level of COL-II at the base of the cartilage in the control group was greatly reduced, while the expression level of MMP-13 was greatly increased. This indicates that the articular cartilage is in a state of high decomposition and low synthesis. Compared with the PN and PCN hydrogel groups, the PCTN double network hydrogel group had a higher expression level of COL-II and a lower expression level of MMP-13, which was closest to the sham group. These results indicate that the PCTN double network hydrogel can effectively protect articular cartilage, alleviate cartilage degeneration, and inhibit the development of osteoarthritis.

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A strong double network hydrogel, characterized in that: It is obtained by freezing and thawing a mixed aqueous solution containing high molecular weight polymers, polysaccharides and polyphenols and immersing it in a salt solution; In the mixed aqueous solution, the concentration of the high molecular polymer is 1-40wt%, the concentration of the polysaccharide is 0.1-10wt%, and the concentration of the polyphenol is 0.1-10wt%.

2. The strong double network hydrogel according to claim 1, characterized in that: The high molecular polymer is selected from one or more of polyvinyl alcohol, gelatin, polyvinyl pyrrolidone, polyglutamic acid and / or hydroxypropyl methylcellulose, preferably polyvinyl alcohol; Preferably, the polysaccharide is selected from one or more of carboxymethyl chitosan, sodium alginate, chitosan, pectin and / or carboxymethyl cellulose, preferably carboxymethyl chitosan; Preferably, the polyphenol is selected from one or more of tannic acid, gallic acid, epigallocatechin gallate, catechin and / or anthocyanidin, preferably tannic acid; Preferably, the salt is selected from one or more of sodium chloride, sodium citrate, sodium sulfate, sodium iodide, sodium carbonate, sodium nitrate, potassium chloride, lithium chloride, calcium chloride and / or magnesium chloride, preferably sodium chloride.

3. The strong double network hydrogel according to claim 1 or 2, characterized in that: In the mixed aqueous solution, the concentration of the high molecular polymer is 10-20wt%, the concentration of the polysaccharide is 0.5-4wt%, and the concentration of the polyphenol is 0.5-4wt%.

4. The strong double network hydrogel according to claim 1 or 2, characterized in that: The high molecular polymer is polyvinyl alcohol, the polysaccharide is carboxymethyl chitosan, and the polyphenol is tannic acid.

5. The strong double network hydrogel according to claim 1 or 2, characterized in that: The high molecular polymer is polyvinyl alcohol, the polysaccharide is carboxymethyl chitosan, and the polyphenol is tannic acid; In the mixed aqueous solution, the concentration of polyvinyl alcohol is 20 wt %, the concentration of carboxymethyl chitosan is 3 wt %, and the concentration of tannic acid is 2 wt %.

6. A method for preparing the strong double network hydrogel described in any one of 1-5, characterized in that: include: dissolving high molecular polymer, polysaccharide and polyphenol in water to obtain a mixed solution; The mixed solution is subjected to a freeze-thaw method to form a double network hydrogel; The double network hydrogel is immersed in a salt solution to obtain a strong double network hydrogel.

7. The preparation method according to claim 6, characterized in that: The stirring is carried out at 85-95° C. for 1-6 h, preferably for 4 h.

8. The preparation method according to claim 6, characterized in that: The freezing is performed at -20°C for 6-24 hours, preferably at -20°C for 12 hours; Preferably, the thawing is thawing at 25°C for 2-12 hours, preferably thawing at 25°C for 6 hours.

9. The preparation method according to claim 6, characterized in that: The salt is selected from one or more of sodium chloride, sodium citrate, sodium sulfate, sodium iodide, sodium carbonate, sodium nitrate, potassium chloride, lithium chloride, calcium chloride and / or magnesium chloride, preferably sodium chloride; Preferably, the concentration of the sodium chloride solution is: 1-5.43 mol / L, more preferably 5.43 mol / L; Preferably, the double network hydrogel is immersed in the saline solution for 1-24 hours, more preferably for 12 hours.

10. Use of the strong and tough double network hydrogel according to any one of claims 1 to 5 or the strong and tough double network hydrogel prepared by the preparation method according to any one of claims 6 to 9 in preparing a soft supporting tissue scaffold; Preferably, the soft supporting tissue scaffold comprises a meniscus substitute.